(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A co-operative bank is an institution which is owned by its members. They are the culmination of efforts of people of same professional or other community which have common and shared interests, problems and aspirations. They cater to services like loans, banking; deposits etc. like commercial banks but widely differ in their values and governance structures. They are usually democratic set-ups where the board of members is democratically elected with each member entitled to one vote each. In India, they are supervised and controlled by the official banking authorities and thus have to abide by the banking regulations prevalent in the country. The objectives of co-operative bank are to provide short term and medium term loan to it members for agricultural purposes. The main objective of this study is to find out the customer satisfaction level towards services provided by these banks in Jabalpur city. To analyze the collected data ANOVA test is applied.